Effects of Patriotism and Celebrity Endorsement in Military Advertising. (2nd September 2016) - Park, Sejin; Avery, Elizabeth Johnson
ABSTRACT: This study investigates the influence of patriotism and celebrity endorsement on advertising effectiveness. College students ( N = 201) participated in a 2 × 2 (patriotism: high vs. low × congruence between a celebrity and the military: high vs. low) experiment. To manipulate the subjects' patriotism levels, two video clips were used and to induce congruence, two versions of U.S. Army advertisements were created. The results indicate that patriotism and congruence combined affect advertising effectiveness by increasing favorable attitudes toward military advertising, attitudes toward the military, and behavioral intentions to provide positive word of mouth (WOM) regarding the military.